Migratory stomatitis in soft palate - case report - Guesser, Lucas Fernando; Zavadinack, Matheus; Lima, Antonio Adilson Soares de (Journal of Oral Diagnosis, 2022)
Introduction: Migratory stomatitis is a benign disorder of unknown cause. Lesions are characterized by erythematous erosive areas with irregular gray-white borders. The margins are slightly protruding and resemble the contours of a geographic map. Lesions of migratory stomatitis can affect different anatomical regions. Objective: The objective of this work is to report a case of migratory stomatitis in the soft palate. Case report: A 20-year-old male presented with geographic tongue and migratory stomatitis in the soft palate. Conclusion: Migratory stomatitis can also affect atypical anatomical regions (such as the soft palate) of individuals without a history of stress and anxiety.